1988
DOI: 10.1007/bf00582516
|View full text |Cite
|
Sign up to set email alerts
|

Tissue extract recovers cardiac calcium channels from ‘run-down’

Abstract: Effects of cardiac-tissue extract on the activity of L-type Ca2+ channels were investigated in guinea-pig ventricular myocytes with the patch-clamp method. In most patches, Ca2+-channel current recorded with a pipette solution containing 50 mM Ba2+ and 3 microM Bay K 8644 ran down within 5 min after excision of the patches into a solution containing EGTA. This run-down of Ca2+ channels was prevented when patches were excised into a solution containing a supernatant fraction of homogenate of guinea-pig or bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 10 publications
6
37
0
Order By: Relevance
“…Consistent with the above finding, under perforated patch configuration, isoprenaline (500 nÒ) induced a 3-to 5-fold increase in ICa,L. Under perforated patch configuration, isoprenaline responses to ICa,L are maintained for longer periods of time compared with the conventional whole cell configuration (Kameyama, Kameyama, Nakayama & Kaibara, 1988;Belles, Malecot, Hescheler & Trautwein, 1988). In the present experiments, the response of ICa,L to the â_agonist isoprenaline remained largely unaltered for at least 20 min in control experiments.…”
Section: Discussion Et_1 and Basal Ical Activitysupporting
confidence: 69%
“…Consistent with the above finding, under perforated patch configuration, isoprenaline (500 nÒ) induced a 3-to 5-fold increase in ICa,L. Under perforated patch configuration, isoprenaline responses to ICa,L are maintained for longer periods of time compared with the conventional whole cell configuration (Kameyama, Kameyama, Nakayama & Kaibara, 1988;Belles, Malecot, Hescheler & Trautwein, 1988). In the present experiments, the response of ICa,L to the â_agonist isoprenaline remained largely unaltered for at least 20 min in control experiments.…”
Section: Discussion Et_1 and Basal Ical Activitysupporting
confidence: 69%
“…Therefore, CS or its domain L may not be unique player to maintain the channel activity in the intact cell, as suggested previously (3)(4)(5)(6)(7)(8). In our previous reports, Ca 2ϩ channel activity was restored to about 64 -86% of the activity in cell-attached condition by crude cytoplasm or a solution containing ATP, CS, and H fraction, a chromatographically-separated high molecular fraction from bovine heart cytoplasm (8,21).…”
Section: Discussionsupporting
confidence: 51%
“…Figure 2B shows an example of the effect of domain 1. The chan- 3.3% of that in the cell-attached mode after the patch was excised. When 25 ⌴ domain 1, supplemented with 3 mM ATP, was applied, further run-down was not prevented, unlike full-length CS.…”
Section: Effect Of Cs Domain 1 On Ca 2ϩ Channel Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work also shows that phosphatidylinositol-4,5-bisphosphate (PIP 2 ) can stabilize the activity of P / Q-type Ca 2+ channels (5,6). Alternatively, we have reported that a cytoplasmic extract from cardiac tissue recovers the Ca 2+ channel activity from run-down (3,7,8), suggesting that run-down of the Ca 2+ channel activity may be due to the washout of certain cytoplasmic factors. Subsequently the cytoplasmic factors were identified as calpastatin, ATP, and a yet unidentified factor in a high molecular mass fraction (H fraction) obtained from gel filtration of the cardiac tissue (3,9,10).…”
Section: Introductionmentioning
confidence: 96%